Integration of Genetic Resources and Intellectual Property Rights within Global and Islamic Legal Frameworks - Shakar, Rana Saad; Najim, Samah Riyadh; Kabrch, Jassim Kadhi; Turchyn, Maryna (Al-Istinbath: Jurnal Hukum Islam, 2024)
The article evaluates international legal frameworks governing genetic resources and intellectual property rights (IPR), with a focus on their alignment with Islamic legal principles. Given the rapid advancements in biotechnology, genetic resources have become critical assets, raising complex issues related to ownership, use, and equitable allocation, particularly within Islamic contexts. The study conducts a thorough analysis of international agreements, including the Convention on Biological Diversity (CBD), the Nagoya Protocol, and the Trade-Related Aspects of Intellectual Property Rights (TRIPS) Agreement, alongside core Islamic legal texts. Through examining case law, policy developments, and academic scholarship, the study highlights key tensions, as the CBD and Nagoya Protocol prioritize fair resource distribution and conservation, while TRIPS emphasizes IPR protection, often restricting resource access. Islamic principles such as justice ('Adl'), fairness ('Ihsan'), and stewardship ('Amanah') are explored as foundational ethics that can inform a balanced framework for IPR and resource distribution. Findings indicate that integrating Islamic values with international policies can promote a fairer and more ethical system, ensuring equitable compensation for all stakeholders, especially indigenous and marginalized communities. The study concludes that a unified legal framework rooted in both international and Islamic values is essential to achieve a just balance between IPR protection and the equitable sharing of genetic resource benefits.